Anti-cancer effects of Rhizoma Curcumae against doxorubicin-resistant breast cancer cells - Zhangfeng Zhong; Haibing Yu; Shengpeng Wang; Yitao Wang; Liao Cui (BMC, 2018)
Abstract Background Chemotherapy is a primary approach in cancer treatment after routine surgery. However, chemo-resistance tends to occur with chemotherapy in clinic, resulting in poor prognosis and recurrence. Nowadays, Chinese medicine may shed light on design of new therapeutic modes to overcome chemo-resistance. Although Rhizoma Curcumae possesses anti-cancer activities in various types of cancers, the effects and underlying mechanisms of its bioactive components against chemo-resistance are not clear. Therefore, the present study aims to explore the potential effects of Rhizoma Curcumae on doxorubicin-resistant breast cancer cells. Methods The expression and function of ABC transporters in doxorubicin-resistant MCF-7 breast cancer cells were measured by western blotting and flow cytometry. Cell viability was detected using MTT assay. The combination index was analyzed using the CalcuSyn program (Biosoft, Ferguson, MO), based on the Chou-Talalay method. Results In our present study, P-gp was overexpressed at protein level in doxorubicin-resistant MCF-7 cell line, but short of MRP1 and BCRP1. Essential oil of Rhizoma Curcumae and the main bioactive components were assessed on doxorubicin-resistant MCF-7 cell line. We found that the essential oil and furanodiene both display powerful inhibitory effects on cell viability, but neither of these is the specific inhibitor of ABC transporters. Moreover, furanodiene fails to enhance the efficacy of doxorubicin to improve multidrug resistance. Conclusion Overall, our findings fill the gaps of the researches on chemo-resistance improvement of Rhizoma Curcumae and are also beneficial for Rhizoma Curcumae being developed as a promising natural product for cancer adjuvant therapy in the future.